Pengaruh Pelatihan dan Kompetensi Trainer terhadap Kinerja Karyawan PT.PLN (PERSERO) Rayon Manahan - Ladina, Andritya; , Jati Waskito S.E., M.Si (2015)
This study aims to analyze how much influence the variables of training and competence of trainers on the performance of employees of PT. PLN (Persero) Rayon Manahan. The population in this study are employees of PT. PLN (Persero) Rayon Manahan, while samples in this study 38 employees of PT. PLN (Persero) Rayon Manahan with the sampling method used in this study is a non probality sample by not providing equal opportunity for each element or member of the population to be sampled. Methods of research data analysis using multiple linear regression, whereas the hypothesis test using the F test, t test, and determinasi coefficient (R2). Based on the results of the study indicate that the training and trainer competence significantly influence the performance of employees of PT. PLN (Persero) Rayon Manahan. Keywords: training, competency, trainer, performance